Tourist Geographic Information System in Baturaden - Krisna Subarkah; Muhammad Lulu Latif Usman (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
As the largest archipelago country in the world, Indonesia has many tourist attractions. One of the tours in Indonesia is tourism in the Baturaden area. To increase tourism promotion and management, a supporting application is needed, one of which is by using WebGIS. This WebGIS application is then used as a medium for spatial information for mapping tourism in Baturaden. The method used in this research is to use the Agile model development method using BlackBox testing. The results of this study are in the form of a WebGIS application prototype for tourism mapping in Baturaden, which is declared valid using BlackBox testing. As the largest archipelago country in the world, Indonesia has many tourist attractions. One of the tours in Indonesia is tourism in the Baturaden area. To increase tourism promotion and management, a supporting application is needed, one of which is by using WebGIS. This WebGIS application is then used as a medium for spatial information for mapping tourism in Baturaden. The method used in this research is to use the Agile model development method using BlackBox testing. The results of this study are in the form of a WebGIS application prototype for tourism mapping in Baturaden, which is declared valid using BlackBox testing.